Analisis Perencanaan Kebutuhan Bahan Baku untuk Meningkatkan Pencapaian Target Produksi pada UD. Kasak Paper Bag - Amanda Seftia Andini; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. Kasak Paper Bag is a manufacturing company that produces paper bags and experiences problems in controlling and supplying raw materials, especially medium paper, which causes delays in the production process. The raw material procurement system is still based on estimates, resulting in shortages and excess inventory. The purpose of this study is to determine efficient raw material planning through the application of the Material Requirement Planning (MRP) method. The methods used include demand forecasting with the Moving Average and Weighted Moving Average methods with the application of the Lot For Lot (LFL) and Period Order Quantity (POQ) lot sizing techniques. The results show that the Moving Average method has the best level of accuracy with a MAD value of 503.7. MRP calculations show that the LFL method produces the minimum total inventory cost of Rp16,530,000 compared to the POQ method. The application of MRP can increase the effectiveness of raw material inventory management and maintain the smoothness of the production process.